1990
DOI: 10.3109/00365529008997637
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Ambulatory Gastric pH Recordings in the Corpus and Antrum: Effect of Food, Time, and Electrode Position

Abstract: The reproducibility of simultaneous, long-term, ambulatory gastric pH recordings in the antrum and corpus was investigated in nine healthy subjects who underwent three separate, 27-h gastric double pH-metries. Intraindividual reproducibility for the entire 27-h recording period was good in the corpus (Kendall's concordance coefficient, W' = 0.6393, p less than 0.025) but not in the antrum (W' = 0.4806, NS). Analysis of predefined time periods showed that non-meal daytime pH was reproducible in the corpus (W' =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 13 publications
2
32
0
Order By: Relevance
“…Parietal cells also secrete concentrated HCl, which presumably results in more frequent exposure to acid in the corpus. The pH of the corpus, however, is not lower overall than that of the antrum, although it does display a broader range (8,32,51). Thus, the different regions of the stomach possess distinct physiological characteristics that likely present H. pylori with different chemotactic signals.…”
Section: Discussionmentioning
confidence: 96%
“…Parietal cells also secrete concentrated HCl, which presumably results in more frequent exposure to acid in the corpus. The pH of the corpus, however, is not lower overall than that of the antrum, although it does display a broader range (8,32,51). Thus, the different regions of the stomach possess distinct physiological characteristics that likely present H. pylori with different chemotactic signals.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to the slight alkalinity of the fasting python's stomach, mammals maintain a highly acidic environment (pH 1.1-3) within their stomachs between bouts of digestion (Youngberg et al, 1985;Evans et al, 1988;Cilluffo et al, 1990;Viani et al, 2002). Whereas pythons experience a dramatic postprandial decrease in gastric pH, the luminal pH of mammal stomachs increases rapidly after feeding to range between 3 and 6, presumably as the ingested meal buffers the gastric acid (Savarino et al, 1988;McLauchlan et al, 1989;Cilluffo et al, 1990). Within a few hours after feeding, intragastric pH of mammals drops as acid production, which has increased 20-fold, overwhelms the buffering capacity of the food, which is then being passed through the pyloric sphincter into the small intestine (Fordtran and Walsh, 1973).…”
Section: Gastric Phmentioning
confidence: 99%
“…Fackler et al demonstrated that positioning the probe in the fundus was the optimal position for measurement of gastric pH, whereas Cilluffo et al showed in postprandial states pH measurement in the antrum was more dependable. 41,42 The probe can be placed with the help of fluoroscopy or manometrically with the latter method being commonly used (10 cm below the upper margin of the Lower Oesophageal Sphincter). 43 However, this method is invasive, uncomfortable and can lead to restriction in activity and diet of patients.…”
Section: -38mentioning
confidence: 99%